2021
DOI: 10.1123/jsr.2020-0105
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Tissue Flossing Around the Upper Thigh on Neuromuscular Performance: A Study Using Different Degrees of Wrapping Pressure

Abstract: Context: It has been recently demonstrated that tissue flossing around the ankle joint can be effectively used to improve ankle range of motion, jump, and sprint ability. However, there is a lack of studies investigating the acute effects of tissue flossing applied using different wrapping pressures. Objective: To investigate the acute effects of tissue flossing and the degree of floss band pressure, around the upper thigh on knee range of motion, strength, and muscle contractile characteristics. Design: Cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Konrad mentioned that wrapping flossband around the thigh significantly improved MVC of knee extension compared to the control group (d = 0.77), but leg muscle activation was not found in this study [32]. Vogrin [16] and Vogrin [27] pointed out that wrapping flossband around the thigh provided small to medium benefits to improve isometric MVC of knee extension force compared to the control group, and it significantly increased isometric MVC of knee extension and rectus femoris muscle contraction time after flossing. The underlying physiological mechanisms of flossband on the aspect of force production and muscle activation have yet to be determined, but available evidences showed that there are several viewpoints of using flossband to improve force production mechanism as well as improve neuromuscular function.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Konrad mentioned that wrapping flossband around the thigh significantly improved MVC of knee extension compared to the control group (d = 0.77), but leg muscle activation was not found in this study [32]. Vogrin [16] and Vogrin [27] pointed out that wrapping flossband around the thigh provided small to medium benefits to improve isometric MVC of knee extension force compared to the control group, and it significantly increased isometric MVC of knee extension and rectus femoris muscle contraction time after flossing. The underlying physiological mechanisms of flossband on the aspect of force production and muscle activation have yet to be determined, but available evidences showed that there are several viewpoints of using flossband to improve force production mechanism as well as improve neuromuscular function.…”
Section: Discussionmentioning
confidence: 54%
“…Over the past few years, flossband application has been more commonly used in the field of training or rehabilitation. Accordingly, researchers have concentrated on testing the effects of flossband application on joint ROM in different joints [7,8], muscle tightness [9,10], muscle strength [15,16], as well as physical function performance [8,[11][12][13]. However, despite the apparent benefits found in the above parameters, there was no relevant literature review that integrated these different findings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prill [10] focused on reducing the effort-induced muscle pain (delayed-onset muscle soreness (DOMS)) by flossing. Similarly, a number of new studies evaluated the effect of flossing on the range of motion [17][18][19][20].…”
Section: The Flossing Methodsmentioning
confidence: 99%